Analisis Rekonsiliasi Fiskal atas Laporan Keuangan Komersial dalam Menentukan Pajak Penghasilan (Pph) Terutang berdasarkan UU Perpajakan pada PT MAYORA INDAK Tbk Tahun 2017 - Riri Rumaiza; Rizky Tri Santoso (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2020)
The Object of this study was PT. Mayora Indah Tbk, a Tbk company that is engaged in food and beverage. The purpose of this study was to determine the value of income tax payable by the company, with reconciling commercial financial statements to the fiscal financial statements. By doing reconciliation, company did not need to create two bookkeeping for different purposes. The company just made corrections to items that were not in accordance with the provisions of the tax. Positive correction would increase taxable income, a negative correction would decrease taxable income. This research, analyzed data with descriptive method. It describes the financial statements of the phenomena that was happened by collecting data, calculating income tax, fiscal correction in accordance with UU Number 36 Year 2008. Type of data which used are primary data and secondary data. The result of this research is fiscal reconciliation of financial report of PT. Mayora Indah Tbk Year 2017 through positive fiscal correction (fiscal) equal to Rp. 113.417.699.446,- and negative fiscal correction (correction) of Rp. 37.906.597.632,- in the resulting income statement of the company. changes in the value of net income before tax (Taxable Income) from Rp. 905.547.589.704,- to Rp. 981.058.691.518,-.